Analisis Balik Kestabilan Lereng Dengan Menggunakan Metode Bishop yang Disederhanakan Pada Area Blok Bukit Tambun PT. Cahaya Bumi Perdana, Kota Sawahlunto - Rizaldi Rizaldi; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. In December 2019 there was an avalanche on the slope of access road to the mining site block Bukit Tambun. The avalanche resulted in a tunnel of BT 05 and an access road to the BT 04 tunnel covered with avalanche material. Analysis of the security Factor values (FK) and the geometry recommendations of slopes using the Bishop Simplified method. The result of the research is that the first avalanche on the block Bukit Tambun area is a field avalanche (circular failure) with the direction N140oE/70o. Second, The physical and mechanical properties of the Claystone Rocks test get the original fill weight of 14.14 KN/m3, the saturated content weight value of 18.6 KN/m3, the cohesion (c) = 7.1 kN/m2 and the inner sliding angle (φ) = 73.55 °. Third, recommend the geometry of slopes for dry conditions with a single slope angle of 65° while the overall slope angle of 37°, for the geometry of the slope in a saturated condition with a single slope angle of 25° while the overall slope angle of 18° and a condition slope of a half saturated conditions with a single slope angle 34° while the overall slope angle of 23°. Keywords: The Field of Diskontinu, Physical and Mechanical Properties of The Rocks, The Geometry of Slope, Reverse Analysis, Bishop Simplified, The Security Factor.